Kembang goyang characterization with rice - mocaf flour (modified cassava flour) subtitution and variation of milk types : Karakteristik kembang goyang dengan substitusi tepung beras - tepung mocaf (modified cassava flour) dan variasi jenis susu - Dhea Sekar Aulia; Akhmad Mustofa; Merkuria Karyantina (Fakultas Sains dan Teknologi Unisri, 2025)
A traditional cake from Betawi known as kembang goyang is created by shaking it in hot oil until the dough releases from the mold and gets its name from the way it looks budding flowers. In this study, rice flour substitute with mocaf flour and several types of milk were also used. This studied aims to manufacture kembang goyang that are rich in protein, and the optimal of crunchiness, this study attempts to establish the ideal ratio of rice flour to mocaf flour and different types of milk. This study was carried out utilizing a factorial Completely Randomized Design (CRD) consisting of two factors, namely the ratio of rice flour to mocaf flour (30%: 70%, 40%: 60%, 50%: 50%) and variations in the type of milk (goat's milk, cow's milk and soy milk). Kembang goyang substitutions50% rice flour: 50% mocaf flour with the soy milk variation had moisture content of 0,83%, ash 0,78%, fat 41,36%, protein 6,06%, carbohydrate 51,99%, broken white 1,72%, slightly milk 2,84%, milk smell 3,12%, crispy 3,77. Kembang goyang is a substitute rice flour with mocaf flour and a variation of milk that are rich in protein so it has the potential to be a healthy and nutritious food.